Validation of the HITRAN 2016 and GEISA 2015 line lists using ACE-FTS solar occultation observations. (October 2019) - Olsen, K.S.; Boone, C.D.; Toon, G.C.; Montmessin, F.; Fedorova, A.A.; Korablev, O.; Trokhimovskiy, A.
Highlights: Updated versions of GEISA 2015 and HITRAN 2016 line lists are validated using terrestrial solar occultation spectra from ACE-FTS. Spectroscopic parameters for CO2 and H2 O are improved in both line lists. The primary difference we observe between the two line lists comes from O3 absorption features near 3850 cm − 1 and from several CH4 absorption lines in the regions 2800–3200 cm − 1 and 4000–4300 cm − 1 . Abstract: The ExoMars Trace Gas Orbiter (TGO) began its nominal science phase at Mars in April 2018, following releases of editions to two major spectroscopic line lists: GEISA 2015 (Gestion et Etude des Informations Spectroscopiques Atmosphériques: Management and Study of Atmospheric Spectroscopic Information), and HITRAN 2016 (High Resolution Transmission). This work evaluates both line lists over the spectral region between 2325–4350 cm − 1 using terrestrial solar occultation observations made by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS). This spectral region is targeted on Mars by two complementary solar occultation instruments on TGO that will monitor temperature and pressure, aerosols, the abundance of CO2, CO, H2 O, HDO, CH4, and other undetected trace gases. Major updates to GEISA 2015 and HITRAN 2016, with respect to previous editions, have been focused on CO2 absorption features in support of Earth-observing missions to monitor greenhouse. Since CO2 is the dominant absorber on Mars, making up 96.5% of the atmosphere, validating the updated line lists is critically important before their deployment for ExoMars. We report that updated CO2 parameters make significant improvements to spectral fits made when using both line lists. Several updates to H2 O lines in both line lists also show improvement. The primary difference we observe between the two line lists comes from O3 absorption features near 3850 cm − 1 and from several CH4 absorption lines in the regions 2800–3200 cm − 1 and 4000–4300 cm − 1 . Because of these differences, we find that using HITRAN 2016 tends to result in better spectral fits, especially below 30 km, than using GEISA 2015 in this spectral region. Differences are strongly reduced with increasing altitude ( > 40 km) as pressure and gas abundance falls off. It was also discovered that several new errors in both new editions of GEISA and HITRAN were introduced since the HITRAN 2012.